What Constitutes "Too Big to Jail?" Evidence from South Korea's Family Business Groups1. (16th December 2018) - Choi, Hansoo; Kang, Hyoung‐Goo; Lee, Changmin
Abstract: This paper investigates the judicial bias in favor of large economic organizations. The Korean judiciary is biased towards chaebols (large family business groups). Convicted chaebol ‐related defendants receive 9.9% more jail‐sentence suspensions and 19 months shorter jail terms than non‐ chaebol counterparts do. Observed leniency remains robust after controlling for the quality of defense attorneys and other sentencing related factors. Then, we explore what drives the bias. We present two possible explanations. The first explanation is that the larger the chaebol, the larger the judicial bias, implying that the chaebol bias is stronger for top 10 business groups than for other chaebols . The second explanation is that in‐group transactions account for much of the bias. This suggests that the judiciary widely accepts a defense of chaebol offenders to wrongdoings that illegal in‐group transactions are for the interest of entire business group, not for their private gain.